Fiscal shocks and real rigidities - Francesco Furlanetto; Martin Seneca (Danmarks Nationalbank, 2008)
In this paper we show that empirically plausible results on the effects of fiscal shocks in Galí, López-Salido and Vallés (2007) rely on a high degree of price stickiness and a large percentage of financially constrained agents. Real rigidities in the form of habit persistence, fixed firm-specific capital and Kimball demand curves interact in interesting ways with nominal and financial rigidities and allow us to reproduce the same consumption multiplier as Galí et al. (2007) under only two and a half quarters of price stickiness, instead of four, and only 30 per cent of constrained agents instead of 50 per cent. Therefore, real rigidities are useful in the study of fiscal shocks in addition to monetary and productivity shocks as has been shown in the previous literature.
Keywords: E32; E62; 330; rule-of-thumb consumers; fiscal shocks; nominal rigidities; real rigidities; firm-specific capital; habit persistence; Kimball demand curves; Gesamtwirtschaftlicher Konsum; Konsumentenverhalten; Schock; Finanzpolitik; Preisrigidität; Theorie